2002
DOI: 10.1007/3-540-46122-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Invitation to Quantum Dynamical Semigroups

Abstract: The theory of quantum dynamical semigroups within the mathematically rigorous framework of completely positive dynamical maps is reviewed. First, the axiomatic approach which deals with phenomenological constructions and general mathematical structures is discussed. Then basic derivation schemes of the constructive approach including singular coupling, weak coupling and low density limits are presented in their higly simplified versions. Two-level system coupled to a heat bath, damped harmonic oscillator, mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 47 publications
(123 reference statements)
0
42
0
Order By: Relevance
“…To rationalize, one should notice that the coherence in cat states composed of a superposition of two coherent states in a single mode does not represent entanglement. Therefore, this phase loss does not characterize decoherence in accordance with Alicki's notion [34]. Moreover when a pure dephasing term was added it was found that it did not erode the phase coherence between cat states [51].…”
Section: A the Similaritiesmentioning
confidence: 78%
See 1 more Smart Citation
“…To rationalize, one should notice that the coherence in cat states composed of a superposition of two coherent states in a single mode does not represent entanglement. Therefore, this phase loss does not characterize decoherence in accordance with Alicki's notion [34]. Moreover when a pure dephasing term was added it was found that it did not erode the phase coherence between cat states [51].…”
Section: A the Similaritiesmentioning
confidence: 78%
“…The first difficulty is that there are different approaches to the definition of decoherence. Alicki [34] identifies pure decoherence (dephasing) with the decay of the off-diagonal elements of the density operator, which is not accompanied by dissipation. He then argues that dephasing cannot be caused by a harmonic oscillator bath with a coupling, which is linear in coordinates or momenta.…”
Section: Correlated Versus Uncorrelated Statesmentioning
confidence: 99%
“…It is widely accepted that master equations gives a good description of the degrees of freedom of a small system in certain limiting regimes. In the physics literature, this limiting regime is characterized by the Born-Markov approximation and the rotating wave approximation, see [2,12] for a review. Another name, common especially in the mathematical physics literature, is the weak coupling limit, which makes these two approximations exact.…”
Section: Weak Coupling Limitmentioning
confidence: 99%
“…The irreversible character of the L-GKS equation is well known and indicated by the semi-group character of the evolution operator [43,44,15,45]. The generator of the dynamics L is therefore non hermitian.…”
Section: Discussionmentioning
confidence: 99%